Birth-and-Death Evolution of the Fatty Acyl-CoA Reductase (FAR) Gene Family and Diversification of Cuticular Hydrocarbon Synthesis in Drosophila. (10th May 2019) - Finet, Cédric; Slavik, Kailey; Pu, Jian; Carroll, Sean B; Chung, Henry
Abstract: The birth-and-death evolutionary model proposes that some members of a multigene family are phylogenetically stable and persist as a single copy over time, whereas other members are phylogenetically unstable and undergo frequent duplication and loss. Functional studies suggest that stable genes are likely to encode essential functions, whereas rapidly evolving genes reflect phenotypic differences in traits that diverge rapidly among species. One such class of rapidly diverging traits are insect cuticular hydrocarbons (CHCs), which play dual roles in chemical communications as short-range recognition pheromones as well as protecting the insect from desiccation. Insect CHCs diverge rapidly between related species leading to ecological adaptation and/or reproductive isolation. Because the CHC and essential fatty acid biosynthetic pathways share common genes, we hypothesized that genes involved in the synthesis of CHCs would be evolutionary unstable, whereas those involved in fatty acid-associated essential functions would be evolutionary stable. To test this hypothesis, we investigated the evolutionary history of the fatty acyl-CoA reductases (FARs) gene family that encodes enzymes in CHC synthesis. We compiled a unique data set of 200 FAR proteins across 12 Drosophila species. We uncovered a broad diversity in FAR content which is generated by gene duplications, subsequent gene losses, and alternative splicing. We also show that FARs expressed in oenocytes and presumably involved in CHC synthesis are more unstable than FARs from other tissues. Taken together, our study provides empirical evidence that a comparative approach investigating the birth-and-death evolution of gene families can identify candidate genes involved in rapidly diverging traits between species.